Application of Blast Marketing Communication Strategy in Increasing Compliance with Contribution Payments for Wage Recipient Workers (PU) at The Bantul Branch Office of BPJS Ketenagakerjaan - Bella Dian Novitasari; Erlita Ridanasti (International Journal of Economics, Business and Innovation Research, 2024)
The blast marketing communication strategy has become one of the effective marketing communication strategies in increasing compliance with contribution payments. Social security programs like BPJS Ketenagakerjaan play an important role in protecting workers; however, compliance with contribution payments remains low, posing a challenge that must be addressed to ensure the sustainability of the program. This internship final project aims to identify communication strategies that can be implemented to enhance compliance with contribution payments. This final project employs a qualitative approach to collect data through observations, in-depth interviews, and documentation. The implementation of blast marketing has shown to assist in increasing participants' compliance in fulfilling their contribution obligations. From February to June 2023, there was a 1.57% increase in contribution payments. This increase indicates an improvement in the stability and orderliness of contribution payments. Therefore, it is hoped that the stability and orderliness of contribution payments can be maintained to uphold the quality and services for all participants, thereby maximizing the social security program.